Innate-like CD4 T cells selected by thymocytes suppress adaptive immune responses against bacterial infections - Qiao, Yu (2011)
We have reported a new innate-like CD4 T cell population that expresses cell surface makers of effector/memory cells and produce Th1 and Th2 cytokines immediately upon activation. Unlike conventional CD4 T cells that are selected by thymic epithelial cells, these CD4 T cells, named T-CD4 T cells, are selected by MHC class II expressing thymocytes. Previously, we showed that the presence of T-CD4 T cells protected mice from airway inflammation suggesting an immune regulatory role of T-CD4 T cells. To further understand the function of T-CD4 T cells, we investigated immune responses mediated by T-CD4 T cells during bacterial infection because the generation of antigen specific CD4 T cells contributes to clearance of infection and for the development of immune memory. The current study shows a suppressive effect of T-CD4 T cells on both CD8 and CD4 T cell-mediated immune responses during Listeria and Helicobacter infections. In the mouse model of Listeria monocytogenes infection, T-CD4 T cells resulted in decreasedfrequency of Listeria-specific CD8 T cells and the killing activity of them. Furthermore, mice with T-CD4 T cells developed poor immune memory, demonstrated by reduced expansion of antigen-specific T cells and high bacterial burden upon re-infection. Similarly, the presence of T-CD4 T cells suppressed the generation of antigen-specific CD4 T cells in Helicobacter pylori infected mice. Thus, our studies reveal a novel function of T-CD4 T cells in suppressing anti-bacterial immunity.